Colors in French, American and British Dictionaries - Williams, Krista (Lexikos, 2017)
Colors have senses specific to particular fields such as physics and printing, in addition to senses used in everyday life. This article examines the specialized information found in color definitions in French, American and British dictionaries. We explore whether specialized and non-specialized definitions are lumped or split, how much scientific information is included, if the information included varies diachronically and/or geographically and if dictionaries are consistent in their labeling of colors as members of a group (primary, spectral, etc.). We found that specialized and non-specialized senses of colors are typically lumped, rather than split. This is contrary to the treatment of other words with both specialized and non-specialized senses in the same dictionaries, suggesting that the line between these senses is not clear for colors. We also found that more specialized information has been included over time in French, American and British dictionaries, but that American dictionaries still include the most. Additionally, American dictionaries are more consistent than dictionaries of the other two nationalities in their labeling of colors as members of a group, both in the labels themselves and in labeling all members of a group. Based on our findings, we make suggestions for defining colors in general use dictionaries.